The Role of Employee Engagement among Millennial Workers on Job Satisfaction and Its Influence on Organizational Commitment: A Study of Manufacturing Companies in Ambon, Indonesia - Leuhery, Ferdy (HM Publisher, 2023)
Job satisfaction is a key element in creating a productive and motivating work environment. Satisfied employees tend to be more productive, creative, and loyal to their company. However, employee engagement, which includes employees' feelings that they have an important role in the organization, is also an important factor in achieving job satisfaction. Therefore, exploring the relationship between employee engagement, job satisfaction, and organizational commitment in manufacturing companies in Ambon is a very relevant research focus. This study is research with a quantitative approach. This study uses primary data obtained from a survey process using a questionnaire, where the survey process was carried out online. The independent variable in this study is organizational commitment (Y). The dependent variables in this study are job satisfaction (X1), work characteristics (X2), organizational commitment (X3), turnover intentions (X4). There is a significant relationship between job satisfaction and employee engagement. There is a significant relationship between work characteristics and employee engagement. There is no significant relationship between employee involvement and turnover intentions. There is a significant relationship between employee involvement and organizational commitment.